Diversification of the plant-specific hybrid glycine-rich protein (HyGRP) genes in cereals - Fujino, Kenji; Obara, Mari; Sato, Koji (Frontiers in Plant Science, 2014)
Plant-specific hybrid proline- or glycine-rich proteins (HyP/GRPs) are involved in diverse gene functions including plant development and responses to biotic and abiotic stresses. The quantitative trait locus, qLTG3-1, enhances seed germination in rice under low-temperature conditions and encodes a member with a glycine-rich motif of the HyP/GRP family. The function of this gene may be related to the weakening of tissue covering the embryo during seed germination. In the present study, the diversification of the HyP/GRP gene family was elucidated in rice based on phylogenetic relationships and gene expression levels. At least 21 members of the HyP/GRP family have been identified in the rice genome and clustered in five regions on four chromosomes by tandem and chromosomal duplications. Of these, OsHyPRP05 (qLTG3-1) and its paralogous gene, OsHyPRP21, had a glycine-rich motif. Furthermore, orthologous genes with a glycine-rich motif and the HyP/GRP gene family were detected in four genome-sequenced monocots: 12 in barley, 10 in Brachypodium, 20 in maize, and 28 in sorghum, using a BLAST search of qLTG3-1 as the query. All members of the HyP/GRP family in these five species were classified into seven main groups, which were clustered together in these species. These results suggested that the HyP/GRP gene family was formed in the ancestral genome before the divergence of these species. The collinearity of chromosomal regions around qLTG3-1 and its orthologous genes were conserved among rice, Brachypodium, sorghum, and maize, indicating that qLTG3-1 and orthologous genes conserve gene function during seed germination.